Iatrogenic Tracheal Injury During Endotracheal Tube Exchange in a COVID-19 Patient: A Case Report - Nguyen, Connie P.; Lee, Jessica J.; Chen, Michelle Y.; Heinz, Eric R.; Diab, Khalil; Pla, Raymond A. (International Journal of Clinical Research, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has increased the need for prolonged intubation and mechanical ventilation. Though a rare complication of mechanical intubation, tracheoesophageal fistulas (TEFs) are severe and life-threatening. We present a patient with COVID-19 pneumonia who developed an iatrogenic TEF suspected to have been acquired during traumatic reintubation. After optimizing her for surgery, management of the TEF included tracheostomy tube placement at the distal end of the tracheal injury and placement of a stent over the defect. CT scan later showed migration of the stent into the esophagus that required removal. Despite receiving supportive therapy, the patients’ status declined and the patient shortly expired. By increasing demand for prolonged mechanical ventilation, complicating intubations amid fears of transmission, and potentially causing inflammatory tracheal damage, COVID-19 creates heightened obstacles to intubation that may put patients at risk of acquiring tracheal injuries. Increased awareness of possible tracheal injuries should be made by considering the many risk factors.